Concepts, Methods and Applications of Quantum Systems in Chemistry and Physics Selected proceedings of QSCP-XXI (Vancouver, BC, Canada, July 2016) (Progress in Theoretical Chemistry and Physics,, 2018)
This edited, multi-author volume contains selected, peer-reviewed contributions based on the presentations given at the 21th International Workshop on Quantum Systems in Chemistry, Physics, and Biology (QSCP-XXI), held in Vancouver, Canada, in July 2016. This book is primarily aimed at scholars, researchers and graduate students working at universities and scientific laboratories and interested in the structure, properties, dynamics and spectroscopy of atoms, molecules, biological systems and condensed matter.